IMPLEMENTASI WEB SERVICE PADA LAYANAN KATALOG PERPUSTAKAAN ONLINE (Information Technology and Telematics, 2014)
AbstrakWeb Service technologies aimed to apply the software reusability and distributed system that canbe accessed by internet and the ease of bridging any information without questioning the use ofdifferences technology. One of the Web services technologies that are being developed is anintegration of several libraries become one in a library catalog web system or commonly knownas OPAC. This development provide a facility that enables for book tracking in various librariessimply by opening a web catalog. This searching or tracking classified by category, title, author,and book publishers .The purpose of this study is to facilitate the search of books in various libraries, so it can give areference of book collection, then raise public awareness and especially students to be moreinterest in reading and visiting the library. The system is built using PHP and MySQL. The use ofREST as a component of Web Service because REST can be easily developed and implemented.Keywords : Web Service; REST; OPAC